NCOA4 linked to endothelial cell ferritinophagy and ferroptosis:a key regulator aggravate aortic endothelial inflammation and atherosclerosis - Li Zhu; Zijian Liu; Jiahui Liu; Zhenglong Li; Youli Bao; Xin Sun; Wenchen Zhao; An Zhou; Hongfei Wu (Redox Biology)
Atherosclerosis (AS) is associated with a high incidence of cardiovascular events, yet the mechanisms underlying this association remain unclear. Our previous study found that Atherosclerotic endothelial injury is closely associated with ferroptosis in ApoE−/− mice. Ferroptosis is a novel mode of cell death induced by decreased antioxidant capacity of the organism and accumulation of reactive oxygen species. Nuclear receptor coactivator 4 (NCOA4)-mediated ferritinophagy is an important regulator of sudden ferroptosis in cells. However, the role of NCOA4 in AS and the exact mechanism by which it regulates the ferritinophagy response remain unclear. Herein, we report that NCOA4 expression is elevated in ApoE−/− mice and endothelial cells and is significantly correlated with AS. NCOA4 expression promoted ferroptosis, and was positively correlated with ferritinophagy response. Mechanistically, our findings indicate that LOX-1 is a key upstream target that influences the function of NCOA4. The specific pathway is related to the activation of cGAS-STING signaling to upregulate NCOA4 expression. Moreover, our findings demonstrate the ''Gualou-Xiebai'' herb pair can regulate LOX-1 to inhibit ferroptosis. Collectively, our results provide evidence of a connection between NCOA4-mediated promotion of AS and suggest that targeting upstream molecules regulating NCOA4 could be a potential therapy for AS.